EVALUASI PENGGUNAAN SISTEM INFORMASI “TEAMMATE” DALAM PELAKSANAAN TUGAS AUDIT PADA INSPEKTORAT JENDERAL KEMENTERIAN KEUANGAN - Aditya Yuda Krisnanto Putra (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2016)
This research is motivated by the use of technology is considered important because it can help the activity or activities of the o.rganization, including the audit field through the use of the Audit Management System (AMS) where the organization is required to prepare a mechanism/infrastructure of modern information technology-based. The subjects of this study is the Inspectorate General as one unit in the Ministry of Finance that the task of implementing internal control and promote public confidence in the Ministry of Finance. Inspectorate General of the Ministry of Finance in 2011 has been working with the company Wolters Kluwer Audit, Risk & Compliance through the use of Teammate Application in order to implement the Audit Management System (AMS). Results from this study showed that the controls applied to the Inspector General of the Ministry of Finance to the security and confidentiality of information on the Teammate Application is very adequate. However, the Inspectorate General of the Ministry of Finance still have to pay attention to the weaknesses arising from the use of commercial systems to support the operations. Keywords: Audit Management System (AMS), Teammate Application, information system.